Gifts, talents and education a living theory approach - Hymer, Barry; Whitehead, Jack; Huxtable, Marie (Wiley-Blackwell, 2009)
Gifts, Talents and Education: A Living Theory Approach is a practical guide for teachers on how to help all their pupils to enhance their gifts and talents in the classroom. Examples reveal how teachers can transform the way education is understood in schools, by relating stories of how they learned about their own gifts and talents. The book explains recent key developments in multimedia representations of social and emotional aspects of learning. These permit the multi-sensory gifts and talents of individual learners to be recognised and developed within a process that enhances t
Keywords: Gifted children : Education; Gifted children : Education : Research